Real-world safety profile of sonidegib: a disproportionality analysis based on the FDA adverse event reporting system - Zhao, Kaidi; Li, Qinxiao; Qin, Miao; Xiao, Shengxiang; Li, Jing; Liu, Jiashu (Frontiers in Oncology, 2025)
BackgroundSonidegib is a novel treatment for locally advanced basal cell carcinoma (LaBCC) with demonstrated efficacy and safety in clinical trials. However, its real-world safety profile remains insufficiently characterized. This study aimed to evaluate the real-world safety of sonidegib by analyzing adverse event (AE) reports from the FDA Adverse Event Reporting System (FAERS), identifying both known and unexpected safety signals.MethodsData for this study were obtained from the FAERS, covering the period from the third quarter of 2015 to the fourth quarter of 2024. Four disproportionality analysis methods were employed to detect positive signals associated with sonidegib, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). Additionally, time-to-onset (TTO) analysis of AEs was conducted, and sensitivity analyses were performed to assess the robustness of the results.ResultsA total of 1,087 Individual Case Safety Reports (ICSRs) involving 2,496 adverse events were included. The analysis confirmed the occurrence of known AEs, such as muscle spasms and myalgia, while also identifying several unexpected AEs, including pneumonia, sepsis, urinary tract infection, and hyperkalemia.ConclusionsThis study analyzed the real-world safety of sonidegib and emphasized the importance of continuous monitoring during the early stages of treatment. These findings provide important safety information for clinicians, but further research is needed to validate these results.